Cleaning house : the fight to rid our homes of toxic chemicals - Dahl, Lindsay (Dey St., an imprint of William Morrow, 2025)
"From the front lines of the movement for safer products, environmental health expert Lindsay Dahl takes us on her journey from skeptic to activist, exposing the secret forces that keep toxic chemicals in our homes, bodies, and environment--showing us how to fight back and keep our families safe."--Provided by publisher.